Contributions of cognitive load theory to understanding information overload: a literature review - de Oliveira Ordonho Sigolo, Brianda; de Castro Silva Casarin, Helen [UNESP] (Universidade Estadual de Campinas, 2024)
Introduction: Information overload (IS) has become a prominent phenomenon in the digital age, where excess information causes cognitive overload. Objective: This study aimed to verify how Information Science studies approach IS related to Cognitive Load Theory (CLT). Methodology: For data collection, a survey of scientific articles and papers presented at events was carried out in the Web of Science and Scopus databases. Twenty-six papers were selected. Using thematic analysis, three thematic categories were identified in the set of papers analyzed: Effects of digital information and communication technologies; Impact on learning; and Misinformation and sharing during the covid-19 period. Results: CLT was used as a theoretical basis for developing conceptual models and testing hypotheses to explain how information systems, through their design and search options, can cause IS. It was also used in the design of learning resources to improve knowledge acquisition and in understanding the misinformation caused by information overload during the covid-19 pandemic. Conclusion: It was concluded that the integration of CLT and IS provides a deeper understanding of the challenges faced by human cognitive capacity, identifying the factors that contribute to IS and the implementation of CLT-based strategies.
Contribuições da teoria da carga cognitiva para compreensão da sobrecarga informacional: uma revisão de literatura
Keywords: Cognitive Load Theory; Cognitive loads; Cognitive overload; Information overload; Literature review